2020
DOI: 10.1101/2020.06.17.158022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The projections of ipRGCs and conventional RGCs to retinorecipient brain nuclei

Abstract: Retinal ganglion cells (RGCs), the output neurons of the retina, allow us to perceive our visual environment. RGCs respond to rod/cone input through the retinal circuitry, however, a small population of RGCs are in addition intrinsically photosensitive (ipRGCs) and project to unique 1 0 targets in the brain to modulate a broad range of subconscious visual behaviors such as pupil constriction and circadian photoentrainment. Despite the discovery of ipRGCs nearly two decades ago, there is still little informatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Together, these data showed an equally dense mRGC projection into both regions of the SCN and a stronger synaptic connection between mRGC and the shell SCN which should still be evaluated further. Agreeing with our observation, early studies also show direct retinal innervation of both the ventral and dorsal SCN (Beier et al, 2020; Hattar et al, 2006). On the contrary, it was reported that the ventral SCN was reported to receive most of the retinal input and transfer this input to the dorsal SCN (Abrahamson & Moore, 2001; Kriegsfeld et al, 2004; Moore et al, 2002; Welsh et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Together, these data showed an equally dense mRGC projection into both regions of the SCN and a stronger synaptic connection between mRGC and the shell SCN which should still be evaluated further. Agreeing with our observation, early studies also show direct retinal innervation of both the ventral and dorsal SCN (Beier et al, 2020; Hattar et al, 2006). On the contrary, it was reported that the ventral SCN was reported to receive most of the retinal input and transfer this input to the dorsal SCN (Abrahamson & Moore, 2001; Kriegsfeld et al, 2004; Moore et al, 2002; Welsh et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…However, this conclusion ignores the fact that it is unknown whether other non-M1 ipRGCs and non-ipRGCs drive or modulate non-image-forming behaviors. Brain regions that play a central role in non-image-forming vision receive diverse ipRGC and non-ipRGC innervation ( Baver et al, 2008 ; Beier et al, 2020 ; Quattrochi et al, 2019 ). The makeup of RGC innervation to non-image-forming brain regions will ultimately influence behavior; for example, genetically ablating the M1 ipRGC abolishes an animal’s ability to photoentrain, but some PLR remains ( Güler et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a series of studies proved that melanopsin-expressing intrinsically photosensitive retinal ganglion cells (ipRGCs) are the sole conduit of photoentrainment ( Berson, 2003 ; Güler et al, 2008 ). In addition to transmitting light information to the suprachiasmatic nucleus (SCN) ( Fernandez et al, 2016 ), ipRGCs send monosynaptic projections to sleep-promoting centers, such as the preoptic area ( Hattar et al, 2006 ; Beier et al, 2021 ), to mediate the acute effects of light on sleep ( Altimus et al, 2008 ; Lupi et al, 2008 ; Zhang et al, 2021 ). Neuromodulatory processes inhibiting ipRGCs are expected to alter light-evoked behaviors mediated by ipRGCs, such as photoentrainment and/or pupillary light reflex (PLR) ( Güler et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%